Perceptions, attitudes and behaviours toward urban surface water quality in Accra, Ghana - Abraham, Ernest M.; Martin, A.; Cofie, Olufunke O. (Emerald Publishing Limited, 2016)
Purpose: The purpose of this paper is to explore people’s perceptions, stated attitudes, and observed and reported behaviour to water and other environmental quality. Design/methodology/approach: The study adopted a mixed method approach. It employed a cross-sectional survey design. Ten communities were selected in Accra and its surrounding communities to indicate various levels of infrastructure provision and environmental quality. Four separate focus group discussions (FGDs) were carried out in each community, with a mixed group of older and young adult men and women, a group of men only, a group of women only, and a group of young adults only. Following the FGDs, further information was obtained through structured household questionnaire survey involving 443 respondents. Findings: Different ideas were employed to explain people’s perceptions of water quality. There were common ideas such as on health, history of water use, perceptions which affect water use, and management of community activities which affect water sources. These ideas which emerged from the focus groups helped participants to assign meaning to their environment. Reported behaviour was influenced by the ability to pay for services, their availability and the influence of shared community norms. Although citizen participation in water and environmental management decision making was very limited, community collective action can be harnessed to enhance water and other environmental management. Originality/value: Adopted an interdisciplinary approach that enabled explanations to phenomenon to emerge from the perspectives of the society rather than views being suggested to them. Thus, resulting in evidence-based issues for intervention.